Communication Activities in Mitoni Events in Layansari Village (Study of Communication Ethnography Regarding Communication Activities at the Mitoni Event in Layansari Village, Gandrungmangu District, Cilacap Regency in requesting the safety of Mother and Child) - Amin, M. Ali Syamsuddin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research was intended to gives a deep about the communicating actifity mitoni event in Layansari village . As for focus problems divided by researchers into some sub micro problems that is the situation communicative, communicative events, and the act of communicative in mitoni event. The Methods used in this study was a qualitative methodology tradition ethnography communication. Research Informant amounted to 4 (four), 1 key informant and 3 suppored informants that selected by Purposive. Data collecting technique through in-depth interviews, non participants observation, study literature, internet searching, and documentation. Technique of data analysis is data Collection, Data Reduction, Data Display, Conclusion Veryfication. The results showed that the Communicative Situation, contained in mitoni event was conducted in the Layansari village at pregnant mother’s home. Communicative events in a mitoni as a cultural tradition which is carried out by pregnant woman that seven months pregnancy for entreating the safety of Mother and Child.  Communicative Action in mitoni is an action which embodies the verbal and nonverbal behavior as an gratitude expression and entreating the safety. The conclusions of this study that the communication activity in mitoni event inherited from their ancestors by hereditary to embody respect for the ancestors and applying the safety of Mother and Child. The advice from researcher in order to always execute when a  pregnant woman that seven months pregnancy in entreating the safety and also to  conservating this culture.